2021
DOI: 10.7150/jca.49944
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of docetaxel plus cisplatin (TP) induction chemotherapy followed by TP concurrent chemoradiotherapy in locoregionally advanced nasopharyngeal carcinoma

Abstract: Objective : To investigate the clinical value of induction chemotherapy (IC) with docetaxel plus cisplatin (TP) followed by concurrent chemoradiotherapy (CCRT) with TP in locoregionally advanced nasopharyngeal carcinoma (NPC). Methods : A total of 544 patients with locoregionally advanced NPC that was newly diagnosed from January 2009 to December 2015 were included in this study. Among these patients, 251 were treated with TP induction chemotherapy followed by CCRT with cispl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Accordingly, in locally advanced lung cancerand esophageal cancer, the concurrent chemoradiotherapy regimen is the use of double-drug regimen containing platinum (15,16). Recently, a retrospective analysis obtained that the treament with double-drug regimen containing platinum for concurrent chemotherapy for NPC was better than single platinum drug but the side effects increased signi cantly (17). Our results suggests that under the premise of induction chemotherapy, concurrent chemotherapy of single platinum drug for NPC may be su cient but need more studies to con rm.…”
Section: Discussionmentioning
confidence: 73%
“…Accordingly, in locally advanced lung cancerand esophageal cancer, the concurrent chemoradiotherapy regimen is the use of double-drug regimen containing platinum (15,16). Recently, a retrospective analysis obtained that the treament with double-drug regimen containing platinum for concurrent chemotherapy for NPC was better than single platinum drug but the side effects increased signi cantly (17). Our results suggests that under the premise of induction chemotherapy, concurrent chemotherapy of single platinum drug for NPC may be su cient but need more studies to con rm.…”
Section: Discussionmentioning
confidence: 73%
“…For example, Zhang et al demonstrated that the IC + CCRT group had a higher incidence than the CCRT group of grade 3/4 neutropenia (28.0% vs. 10.5%), thrombocytopenia (11.3% vs. 1.3%), and anemia (9.6% vs. 0.8%) [ 1 ]. Tao et al reported that the incidence rates of grade 3/4 leukocytopenia and neutropenia were significantly increased in the DP + DP group compared with the DP + DDP group in NPC patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a double-drug regimen containing platinum is used for concurrent chemoradiotherapy in locally advanced lung cancer and esophageal cancer [15,16]. Recently, a retrospective analysis obtained that the treatment with a double-drug regimen containing platinum for concurrent chemotherapy for NPC was better than a single platinum drug, but the side effects increased significantly [17]. Our results suggest that under the premise of induction chemotherapy, concurrent chemotherapy of a single platinum drug for NPC may be sufficient but need more studies to confirm.…”
Section: Discussionmentioning
confidence: 99%